Pesantrenisasi sebagai Pembentukan Spiritualitas Mahasiswa (Studi Kasus Wajib Lulus BTA-PPI di IAIN Purwokerto) - Hidayat, Arif (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
The article attempts to examine about ‘a must to be graduated’ phenomena of al-Qur'an Reading and Writing (BTA) dan The Knowledge of Religious Service Implementation (PPI) at The State Islamic Institute of Purwokerto. This idea may be interesting to review since the materialistic living in global culture has brought anxiety concerning a moral ethics alteration of youth that becomes uncontrolled. From this side, therefore, pesantren (Islamic boarding school) becomes the solution to form spirituality value through BTA-PPI Graduated Compulsory which is programmed educationally by IAIN Purwokerto. Students, who failed BTA-PPI, must